Dual role of pectin methyl esterase activity in the regulation of plant cell wall biophysical properties - Gallemí, Marçal; Montesinos, Juan Carlos; Zarevski, Nikola; Pribyl, Jan; Skládal, Petr; Hannezo, Edouard; Benková, Eva (Frontiers in Plant Science, 2025)
IntroductionAcid-growth theory has been postulated in the 70s to explain the rapid elongation of plant cells in response to the hormone auxin. More recently, it has been demonstrated that activation of the proton ATPs pump (H+-ATPs) promoting acidification of the apoplast is the principal mechanism by which auxin and other hormones such as brassinosteroids (BR) induce cell elongation. Despite these advances, the impact of this acidification on the mechanical properties of the cell wall remained largely unexplored.MethodsHere, we use elongation assays of Arabidopsis thaliana hypocotyls and Atomic Force Microscopy (AFM) to correlate hormone-induced tissue elongation and local changes in cell wall mechanical properties. Furthermore, employing transgenic lines over-expressing Pectin Methyl Esterase (PME), along with calcium chelators, we investigate the effect of pectin modification in hormone-driven cell elongation.ResultsWe demonstrate that acidification of apoplast is necessary and sufficient to induce cell elongation through promoting cell wall softening. Moreover, we show that enhanced PME activity can induce both cell wall softening or stiffening in extracellular calcium dependent-manner and that tight control of PME activity is required for proper hypocotyl elongation.DiscussionOur results confirm a dual role of PME in plant cell elongation. However, further investigation is needed to assess the status of pectin following short- or long-term PME treatments in order to determine if pectin methyl-esterification might promote its degradation as well as the role of PME inhibitors upon PME induction.